Spoof localized surface plasmons metamaterial sensor for non-invasive hemodialysis process monitoring - Jinqing Cao; Yachen Pang; Liwei Wang; Huiming Yao; Jianchun Xu; Ke Bi (APL Materials)
Hemodialysis (HD) is widely considered to be the primary means of kidney replacement therapy for end-stage renal disease, involving millions of patients worldwide. The utilization of continuous non-invasive sensors for blood property detection can achieve an adequacy assessment of the dialysis process, which is of great significance for determining the optimal treatment time, ensuring the treatment effect, and improving the quality of life of patients. In this work, a microwave metamaterial sensor is reported for HD based on spoof localized surface plasmons (LSPs). The spoof LSPs sensor is fabricated from a 21 × 12 × 0.043 mm3 thin film, which is conformally attached to the exterior of the pipeline in the dialysis circuit. This attachment design allows for continuous, non-invasive monitoring of variations in the blood’s permittivity of patients. The proposed sensor design is compatible with standard flexible printed circuit technology, allowing for low-cost and large-scale manufacturing. In the frequency range of 3–6 GHz, three resonance modes based on spoof LSPs can be used for liquid sensing with a maximum sensitivity of 0.39%. This study is expected to foster research and application of microwave metamaterial sensors in the biomedical field.